2023
DOI: 10.19160/e-ijer.1168267
|View full text |Cite
|
Sign up to set email alerts
|

Examination on 21st -Century Skills of Preschool Teachers

Abstract: In the developing and changing world, new technologies, a virtual reality world, and new forms of communication are produced every day. All these developments create the need to develop new skills, not only to exist in the digital world but also to exist in social life and social systems. Early childhood is a sensitive period for skill development in human life. Therefore preschool teachers are one of the most important contributors in raising generations that can adapt to the changing and developing world. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In the study, snowball sampling, one of the non-Probability-based sampling methods, also known as purposeful sampling, was selected (Frank & Snijders, 1994). In-depth semi-structured interviews were used as data collection technique (Kallio et al, 2016;Busetto et al, 2020;Atış-Akyol, 2023). Interviews were conducted between January 1 and December 3, 2022.…”
Section: Methodsmentioning
confidence: 99%
“…In the study, snowball sampling, one of the non-Probability-based sampling methods, also known as purposeful sampling, was selected (Frank & Snijders, 1994). In-depth semi-structured interviews were used as data collection technique (Kallio et al, 2016;Busetto et al, 2020;Atış-Akyol, 2023). Interviews were conducted between January 1 and December 3, 2022.…”
Section: Methodsmentioning
confidence: 99%
“…These reviews aim to synthesize and accumulate the results of primary studies, identify research gaps, and guide future studies. The use of systematic reviews has been observed in various areas of educational technology, including digital technology in preschool education (Atış-Akyol et al, 2023), language teaching and learning (Moorhouse et al, 2023), and early childhood education (Marín-Juarros, 2022). These reviews provide insights into the current situation of technology use in education, the types and features of technology, pedagogical implications, and research gaps.…”
Section: Introductionmentioning
confidence: 99%